Pola Komunikasi Pada Pengembangan Kapasitas Kewirausahaan Petani Sayuran (Kasus Pendampingan Misi Teknik Taiwan di Kabupaten Boyolali dan Bogor) - Cahyono Tri Wibowo; Sumardjo .; Didin Hafidhuddin; Sarwititi S Agung (Jurnal Komunikasi Pembangunan, 2012)
Abstract CAHYONO TRI WIBOWO, Communication Pattern on Vegetable Farmers’ Entrepreneurship Capacity development, Case: Taiwan Technical Mission Assistance. Supervised by SUMARDJO as Head of Supervisory Commission; DIDIN HAFIDHUDDIN and SARWITI S. AGUNG as Commission Members. The objectives of this research were: (1) To analyze  effect of characteristic factors such as social dynamic, physical environment, farmers’ characteristics  and socio-economic environment of entrepreneurship communication patterns of  vegetable farmers in Taiwan's technical missions in two districts in Indonesia. (2) To ensure important factors that will  strongly influence the increasing of entrepreneurship capacity of vegetable farmers in Taiwan's technical missions in two districts in Indonesia. (3) To formulate effective communication pattern for entrepreneurship capacity development efforts of  vegetable farmer in the Taiwan’s technical mission in Indonesia two districts. This research resulted several outputs, namely: (1) Communication pattern of farmers’ entrepreneurship in Taiwan’s technical mission was categorized good enough and significantly influenced by group dimensions i.e membership and group climate on social dynamics. (2) The development of farmers’ entrepreneurship capacity in Taiwan’s technical mission was categorized good and it was directly influenced by  education level characteristics and farmers’ business experiences, it was also influenced by  physical environment on  dimensions of communication infrastructure and technology characteristics, it was significantly influenced by socio-economic environment on dimension of support social system and mass media information, and also significantly affected by family support dimension, institutional support and local knowledge functioning of socio-economic environment and significantly influenced by  dialogic dimension on  farmers’ communication entrepreneurship pattern. (3) Effective communication patterns regarding development of entrepreneurship capacity of  farmers was dialogic communication patterns,and communication pattern itself were strengthened by these factors: social dynamic in  dimensions: on group climate and group dimension of membership. (4)  one of the forms of technical skill, social skill, and managerial skill that  potentially can improve and  compete towards farmers were entrepreneur technical skill, social skill, and managerial skill. By improving their technical skill, social skill, and managerial skill, it was expected farmers were able improve their  productivities, income, autonomous which at the end can develop farmers’ welfare in Indonesia. Keywords: Communication pattern, entrepreneurship, capacity development, vegetable farming